2021
DOI: 10.1080/1028415x.2021.1963068
|View full text |Cite
|
Sign up to set email alerts
|

Acute cognitive performance and mood effects of coffee berry and apple extracts: A randomised, double blind, placebo controlled crossover study in healthy humans

Abstract: Background: The principal polyphenols from coffee berry (chlorogenic acids) and apple (flavanols) have recently been shown to improve mood and increase cerebral blood flow in healthy humans. These effects may underpin the cognitive effects of polyphenols seen previously. Objective: The aim of the present paper was to extend previous research by investigating the effects of coffee berry at high and low doses when combined with apple extract on cognitive performance and mood. Design: This randomised, double-blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…Trials administering coffeeberry extract in isolation to cognitively intact adults are limited; however, similar mood enhancements have been observed following 1100 mg coffeeberry extract [20]. Here, participants reported reduced fatigue/inertia and increased vigour/activity as assessed by POMS, and increased alertness before and during the performance of cognitively demanding tasks.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Trials administering coffeeberry extract in isolation to cognitively intact adults are limited; however, similar mood enhancements have been observed following 1100 mg coffeeberry extract [20]. Here, participants reported reduced fatigue/inertia and increased vigour/activity as assessed by POMS, and increased alertness before and during the performance of cognitively demanding tasks.…”
Section: Introductionsupporting
confidence: 59%
“…The CDB consists of serial subtractions of both 3 s and 7 s, along with a sustained attention task (rapid visual information processing (RVIP)); full descriptors of these tasks can be found within the Supplementary Materials. Nutritional interventions have been found to influence the results of tasks that require a high cognitive load over an extended period, such as CDB, in previous research [3,20,[22][23][24].…”
Section: Cognitive and Mood Assessmentmentioning
confidence: 95%
“…A follow-up study contrasting the cognitive and psychological state effects of 1100 mg coffee berry extract alone, and combined with apple polyphenol extract, found that coffee berry alone increased alertness and vigour and decreased fatigue across the 6 h of post-dose assessments. However, this effect was blunted by the addition of apple polyphenols, although this extract did improve the performance of an executive function task [ 160 ], demonstrating the importance of, where possible, considering the effects of treatment arms in isolation. Brain imaging studies have also demonstrated that drinks containing coffee berry extract (1100 mg) can increase cerebral blood flow in the frontal cortex during cognitive tasks [ 159 ] and increase functional connectivity between brain regions implicated in task performance [ 157 ].…”
Section: Multi-component Caffeinated Productsmentioning
confidence: 99%
“…In addition, our results regarding dietary habits, and especially polyphenol and caffeine consumption, provide correlates for feelings of energy and/or fatigue [ 55 , 56 , 57 ]. A diet that is rich in polyphenols (e.g., cocoa flavanols) improved the feelings of mental fatigue, and even though a clear mechanistic explanation is not known, it is postulated that it is related to the known vasodilatory effects and improvements in endothelial function due to the polyphenols [ 131 , 132 , 133 , 134 , 135 , 136 , 137 ]. Caffeine has been used as a remedy for low energy and high fatigue levels [ 138 , 139 ], with the inter-individual differences reporting on the effect of caffeine on moods [ 140 , 141 , 142 , 143 ].…”
Section: Discussionmentioning
confidence: 99%